Study of Protective Effect of Synthetic Neuropeptide Dalargin Under Cold Stress - Shchenyavsky, Ivan I.; Gulevsky, Oleksandr K. (Problems of Cryobiology and Cryomedicine, 2019)
The effect of the neuropeptide dalargin, which is a synthetic analogue of leu-enkephalins, on the negative processes caused by cold stress, which occur when artificial hypothermia is used in vivo, was studyd. It was shown that dalargin prevents the development of apoptotic processes in the cells of homeothermic animals after cold stress, which manifested itself in a decrease in the degree of DNA fragmentation. In the kidneys and liver of experimental animals subjected to cooling, this attribute of apoptosis and cell necrosis was not detected, and in the intestinal mucosa and spleen the level of DNA fragmentation as a result of cold stress is statistically significant. The preliminary injection of dalargin to rats reduces the degree of DNA fragmentation to values that occurred in animals that were not exposed to cold stress. It is also shown that dalargin prevents the development of adrenal hypertrophy in experimental animals, reduces the degree of involution of the thymus and spleen, and reduces the severity of cold stress-induced ulcerogenesis. The simultaneous injection to animals of an opiate receptor antagonist naloxone eliminated the protective effect of an opiate receptor agonist dalargin. Probl Cryobiol Cryomed 2019; 29(3):Â 246â€“254.